Preservice Elementary Teachers' Perceptions of the Learning and Teaching of Civil Rights - Susanne I. Lapp; Rina Bousalis (Athens Institute for Education and Research, 2023)
Although civil rights have been a major part of United States history, it is often taught within a limited scope in elementary classrooms. As preservice elementary teachers have the potential to build the foundation of youth's participatory citizenship, this study aimed to investigate elementary preservice teachers' perceptions, attitudes, experiences, and background knowledge about civil rights in order to gain insight as to how they understand the content and teaching of civil rights. The findings indicate that while preservice teachers primarily and appropriately viewed civil rights as a matter of equality for all citizens, a majority of participants were unable to recognize significant figures other than those that textbooks commonly mention as contributing to the advocacy of civil rights. Moreover, the data suggested that the topic of civil rights should mainly be taught during middle school - or even later during college. As the study revealed that elementary preservice teachers entering their education program methods courses have contradicting ideas about learning and teaching the topic of civil rights, suggested activities and strategies are offered for preservice teachers to better understand civil rights and create lessons that reflect the diversity in their classroom.